Humoral immune responses mediate the development of a restrictive phenotype of chronic lung allograft dysfunction - Keizo Misumi; David S. Wheeler; Yoshiro Aoki; Michael P. Combs; Russell R. Braeuer; Ryuji Higashikubo; Wenjun Li; Daniel Kreisel; Ragini Vittal; Jeffrey Myers; Amir Lagstein; Natalie M. Walker; et al. (JCI Insight, 2020)
Understanding the distinct pathogenic mechanisms that culminate in allograft fibrosis and chronic graft failure is key in improving outcomes after solid organ transplantation. Here, we describe an F1 → parent orthotopic lung transplant model of restrictive allograft syndrome (RAS), a particularly fulminant form of chronic lung allograft dysfunction (CLAD), and identify a requisite pathogenic role for humoral immune responses in development of RAS. B6D2F1/J (H2-b/d) donor lungs transplanted into the parent C57BL/6J (H2-b) recipients demonstrated a spectrum of histopathologic changes, ranging from lymphocytic infiltration, fibrinous exudates, and endothelialitis to peribronchial and pleuroparenchymal fibrosis, similar to those noted in the human RAS lungs. Gene expression profiling revealed differential humoral immune cell activation as a key feature of the RAS murine model, with significant B cell and plasma cell infiltration noted in the RAS lung allografts. B6D2F1/J lung allografts transplanted into μMt–/– (mature B cell deficient) or activation-induced cytidine deaminase (AID)/secretory μ-chain (μs) double-KO (AID−/−μs−/−) C57BL/6J mice demonstrated significantly decreased allograft fibrosis, indicating a key role for antibody secretion by B cells in mediating RAS pathology. Our study suggests that skewing of immune responses determines the diverse allograft remodeling patterns and highlights the need to develop targeted therapies for specific CLAD phenotypes.